2020
DOI: 10.1093/treephys/tpaa107
|View full text |Cite
|
Sign up to set email alerts
|

Salinity has little effect on photosynthetic and respiratory responses to seasonal temperature changes in black mangrove (Avicennia germinans) seedlings

Abstract: Temperature and salinity are important regulators of mangrove range limits and productivity, but the physiological responses of mangroves to the interactive effects of temperature and salinity remain uncertain. We tested the hypothesis that salinity alters photosynthetic responses to seasonal changes in temperature and vapor pressure deficit (D), as well as thermal acclimation of leaf respiration in black mangrove (Avicennia germinans). To test this hypothesis, we grew seedlings of A. germinans in an outdoor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Previous work at SS has also indicated that salinity can be very high during summer (up to 60 ppt) and lower during winter (48 ppt) (Dangremond et al, 2020). Previous studies have found small increases in R with increasing salinity, presumably due to costs associated with maintaining cellular ion gradients (Aspinwall et al, 2021; Lopez‐Hoffman et al, 2007). Thus, the combination of warmer growth temperatures and higher salinity might explain why R increased with T air at SS, and why temperature acclimation appeared constrained.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous work at SS has also indicated that salinity can be very high during summer (up to 60 ppt) and lower during winter (48 ppt) (Dangremond et al, 2020). Previous studies have found small increases in R with increasing salinity, presumably due to costs associated with maintaining cellular ion gradients (Aspinwall et al, 2021; Lopez‐Hoffman et al, 2007). Thus, the combination of warmer growth temperatures and higher salinity might explain why R increased with T air at SS, and why temperature acclimation appeared constrained.…”
Section: Discussionmentioning
confidence: 93%
“…However, direct measures of leaf R or its temperature sensitivity over space and time are relatively rare for marsh and mangrove species. Only a handful of studies have quantified temperature acclimation of leaf R in mangrove species (see Akaji et al, 2019; Aspinwall et al, 2021) and none have examined temperature acclimation in marsh grasses. As a result, the extent to which temperature acclimation of R leads toward homeostasis of realized (in situ) R over space and time in coastal wetland plants remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, low air temperature (< 20 ℃) significantly reduced photosynthetic capacitythe maximum carboxylation rate and the maximum electron transport rate (Aspinwall et al, 2021); this, in turn, decreased the marginal WUE (ΔAn/ΔE), leading to the downregulation of stomatal conductance, a behavior of mangroves' stomata observed under low temperature conditions (Akaji et al, 2019;Aspinwall et al, 2021). This resulted in the depression of photosynthesis and transpiration during this season.…”
Section: Effects Of Other Factors and Further Model Improvementmentioning
confidence: 98%
“…Tonoplast H + ATPase and vacuolar acid phosphatase production increased along with vacuolar volume in Bruguiera sexangula under salt stress which indicates their importance in vacuolar transport of ions ( Mimura et al., 2003 ). A. marina is also known for its peculiarity to adjust salinity by storing inorganic ions in vacuoles and organic solutes in non-vacuolar spaces, but the genes involved are not studied yet ( Aspinwall et al., 2021 ). Similar to these findings, genes involved in Ca 2+ signaling and thus regulating both cell membrane and vacuolar ion transport are upregulated specifically in B. gymnorrhiza leaf tissues ( Miyama and Tada, 2008 ).…”
Section: Genetic and Molecular Basis Of Mangrove Adaptations To Intertidal Environmentsmentioning
confidence: 99%